KLASIFIKASI STATUS GIZI BALITA DI KELURAHAN OESAPA BARAT MENGGUNAKAN METODE K-NEAREST NEIGBOR - Yampi R Kaesmitan; Jusrianto A Johannis (Universitas Muhammadiyah Ponorogo, 2017)
Nutritional status is a state of the body as a result of food consumption patterns and the use of nutritional substances. Determination of the nutritional status of children is useful to know the circumstances of infant nutritional based BB / U (Weight by Age), TB / U (Height by Age), BB / TB (Weight by Height). The system designed is a system of determining the nutritional status of children using the K-NN (K-Nearest Neighbor), where the method of K-NN (K-Nearest Neighbor) is a method of classifying or grouping of test data that is unknown class to several nearest neighbors using distance calculation formula. The variables used in this system is based on data Anthropometri or measurements of the human body, namely U (Age), BB (Weight), TB (Height), LK (Head Circumference).